CYBERSECURITY IN THE DIGITAL AGE - Xalilova Zarnigor Muhammadjon qizi; Ibrohimov Zikiriyo Muzaffar o‘g‘li (TADQIQOTLAR, 2025)
Abstract:  In  the  digital  age,  cybersecurity  plays  a  crucial  role  in  protecting information, systems, and users from cyber threats. With the rapid expansion of digital technologies,  online  platforms,  and  smart  devices,  the  risk  of  cyberattacks  has significantly increased. This article examines the main challenges and forms of cyber threats, including malware, phishing, data breaches, and identity theft. It also highlights modern  cybersecurity  solutions  such  as  encryption,  multi-factor  authentication, firewalls,  and  user  awareness  training.  The  study  emphasizes  the  importance  of building  a  secure  digital  environment  and  the  need  for  continuous  technological improvement and education to ensure information safety.